2011
DOI: 10.1121/1.3531954
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual weighting of individual and concurrent cues for sentence intelligibility: Frequency, envelope, and fine structure

Abstract: The speech signal may be divided into frequency bands, each containing temporal properties of the envelope and fine structure. For maximal speech understanding, listeners must allocate their perceptual resources to the most informative acoustic properties. Understanding this perceptual weighting is essential for the design of assistive listening devices that need to preserve these important speech cues. This study measured the perceptual weighting of young normal-hearing listeners for the envelope and fine str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 58 publications
9
45
0
Order By: Relevance
“…These data support previous work in the lateral geniculate nucleus (Butts et al, 2011) as well as previous reports from the auditory cortex (Wehr and Zador, 2003;Wu et al, 2008) and somatosensory cortex (Gabernet et al, 2005;Wilent and Contreras, 2005) that suggest that delayed inhibition can enhance stimulus selectivity, spike-timing precision, and reliability. Our work supports the notion that this is a general mechanism in sensory coding, across stages and species.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These data support previous work in the lateral geniculate nucleus (Butts et al, 2011) as well as previous reports from the auditory cortex (Wehr and Zador, 2003;Wu et al, 2008) and somatosensory cortex (Gabernet et al, 2005;Wilent and Contreras, 2005) that suggest that delayed inhibition can enhance stimulus selectivity, spike-timing precision, and reliability. Our work supports the notion that this is a general mechanism in sensory coding, across stages and species.…”
Section: Discussionsupporting
confidence: 81%
“…Our work demonstrates that delayed, spectrotemporally tuned inhibition enhances envelope locking by gain control, leading to the suppression of lowprobability responses. This is important to the discrimination of complex stimuli, such as speech, whose intelligibility has been shown to rely heavily on envelope information (Shannon et al, 1995;Smith et al, 2002;Fogerty, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Signal processing of the experimental sentences was conducted following the procedures described by Fogerty (2011a) and is detailed below. No sentences were repeated from Experiment 1 A.…”
Section: Experiments 1b: Temporal Component Contributions a Methodsmentioning
confidence: 99%
“…Weighting functions obtained indicate the "importance" listeners place on suprathreshold temporal information across the broadband speech signal. Fogerty (2011a) recently demonstrated that this method is able to present the full power spectrum of speech, while using noise to independently mask E and TFS components in different frequency bands. The current study applies this method to investigating perceptual weighting strategies a) Portions of the data were presented at the 162nd Meeting of the Acoustical Society of America [J.…”
Section: Introductionmentioning
confidence: 99%